Anemia Prevention Movement in Adolescents in the Implementation of the GRASS in the Stunting Reduction Program - Lidia Hastuti; Ridha Mardiyani; Ayu Rizky; Nuruniyah; Wien Fitrian. R; Fitrian. R; Thosimah; Yuyun Nisaul K; Tilawati Aprina; Yenni Lukita; Dwi Khalisa (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The prevalence of anemia in women of reproductive age (15-49) in the world in 2019 was around 29.9%, and the prevalence of anemia in non-pregnant women aged 15-49 years was 29.6%, which includes the adolescent age category. Anemia is a major health problem in adolescents, especially teenage girls; if not handled properly, it will continue into adulthood and will contribute greatly to maternal mortality, premature babies, and babies with low birth weight. This condition can trigger the risk of stunting in babies born. Aims: to increase adolescent knowledge about preventing anemia. Method: Peer-educator training for preventing anemia and Simultaneous movement to drink Fe tablets. Results: The activities carried out were Peer educators for the prevention of anemia in adolescents and the simultaneous movement of drinking Fe tablets, followed by female high school/vocational high school students who attend Muhammadiyah charity efforts in 14 districts/cities in West Kalimantan, also female students at 3 PTMA in West Kalimantan, the Aisyiyah Regional Leadership throughout West Kalimantan was attended by 180 participants. The activities were carried out in a Hybrid. Conclusion: The peer educator training activity and the simultaneous movement to drink Fe tablets were carried out with 180 participants (92.3%). The participants' attention until the end of the activity by filling in the activity attendance was 100%. The evaluated participants showed good knowledge with an average score of 97.3 ± SD 3.17 and a commitment statement as peer educators. They will be a source of information that will disseminate information to their other friends at school.